Metodologi Syeikh Nuh Jamaluddin Al-Kelantani Dalam Menghurai Karya Qiraat Syeikh Muhammad Mutawwali Dan Syeikh Ali Dabba’ - Khairul Anuar Mohamad; Abd Muhaimin Ahmad; Mohd Shamsul Hakim Abd Samad (al-Qanatir, 2024)
Indexed by MyCite